Molar distalization with bimetric molar distalization arches - (:unkn) unknown (My University, 1994)
The aim of this study was to observe the clinical and cephalometric effects of intra-oral distalization with the maxillary bimetric arches. 3 girls and 1 boy with a mean age of 13.5 years with Class II skeletal and dental relationship were selected. Care was taken to select patients having a normal vertical growth pattern. Lateral cephalograms were taken at the beginning and at the end of the distalization period, which was approximately 3 months. To observe the distal movement, a metal marker was attached to the distal end of the buccal tube of the first molar. On each lateral cephalometric radiograph a reference plane perpendicular to the occlusal plane and passing through the point Sella was drawn to assess the amount of distalization. Cephalometric measurements indicated that the upper molars moved approximately 3 mm distally and that the lower incisors were proclined.
Keywords: Female; Humans; Adolescent; Male; Malocclusion, Angle Class II; Maxilla; Tooth Movement Techniques; Cephalometry; Orthodontic Appliance Design; Orthodontic Brackets; Molar